KONSTRUK TEOLOGIS ISLAMISME RADIKAL DI INDONESIA PASCA-ORDE BARU - Masdar Hilmy (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstract: Theological Construct of Islamic Radicalism in Post New Order Indonesia. This article seeks to investigate the theological foundation of radical Islamism in post-New Order Indonesia. It basically argues that an attempt at delineating the nomenclature of Islamism from its pejorative connotation becomes imperative in order not to lump such words as pure salafis with salafi jihadist. In addition, the venture of all types of radical Islamism begins with the creed that the establishment of Islamic realm on earth based on the Qur’an and Hadith is a holy duty and regarded as compulsory upon every adult Muslim male. As such, the article analyses 1) the account of belief system of radical Islamism, 2) the transformation process of violence into a sacred creed, and 3) the centrality of such doctrines as jihad and istisyhâd (martyrdom). Kata Kunci: Islamism, radikal, jihad, istisyhâd